Principles of Metacarpal Fracture (Management & Treatment) - Osman, Zaher (Journal for Research in Applied Sciences and Biotechnology, 2022)
The hand is essential in humans for physical manipulation of their surrounding environment. Allowing the ability to grasp, and differentiated from other animals by an opposing thumb, the main functions include both fine and gross motor skills as well as being a key tool for sensing and understanding the immediate surroundings of their owner. Hand fractures are the most common fractures presenting at both accident and emergency and within orthopedic clinics. Appropriate evaluation at first presentation, as well as during their management, can significantly prevent both morbidity and disability to a patient. These decisions are dependent on a wide range of factors including age, hand dominance, occupation, and co-morbidities. A fracture is best described as a soft tissue injury with an associated bony injury. Despite this being the case, this paper intends to deal mainly with the bone injury and aims to discuss both the timing, as well as the methods available, of hand fracture management. Fractures of the metacarpal are the most common of hand fractures accounting for up to 40% [1, 2] and are usually the injury described as ‘a broken hand’ by the general public. For discussion purposes fractures of the metacarpals are best described anatomically and the digits can be grouped together, although the fifth metacarpal is often expressed on its own as the ‘boxer fracture’ and accounts for a quarter of all metacarpal fractures [2]. Likewise, due to anatomical and functional variance the first metacarpal is generally classified as a separate entity which is not included in this Article.